The Implementation Of Story Face Strategy To Improve Students' Reading Comprehension In Narrative Text At UPTD SMP Negeri 9 Parepare - Nurul Zazrina; Nasrullah; Amir Patintingan (La Parole : Journal of Language Teaching and Pedagogy, 2019)
This research focuses on the implementation of the story face strategy to address the students' lack of reading comprehension. Furthermore, the purpose of this research is to find out whether the implementation of story face strategy can improve students' reading comprehension, especially narrative texts in the form of narrative in class VIII UPTD SMP Negeri 9 Parepare. This study uses quantitative methods with pre-experimental classes. Then process of collecting data using pre-test and post-test. The test used was a reading test related to narrative texts about smart parrots, rabbits, and bears, consisting of 10 items, 5 for multiple choice and 5 for essays. Then the sample was selected using simple random sampling, consisting of 20 students from class VIII UPTD SMP Negeri 9 Parepare. The results of the data analysis showed that students' reading comprehension increased significantly. This is indicated by the comparison of the results of the pre-test and post-test. There are only 45.71% of students' scores in the pre-test and 84.28% in the post-test. This means that students' reading comprehension is greater after being given treatment with the story face strategy. This shows that students' reading comprehension at UPTD SMP Negeri 9 Parepare has progressed in learning using this strategy.